PLAN ESTRATÉGICO DE MARKETING PARA PROMOVER EL TURISMO EN EL CANTON VENTANAS, PROVINCIA DE LOS RIOS, AÑO 2022 - Triana Vera, Ayling Rebeca (2022)
The work called "Strategic marketing plan to promote tourism in the Canton Ventanas province of Los Ríos year 2022" is carried out with the objective of developing a strategic marketing plan to promote tourism in the place, through a situational tourism diagnosis, in which marketing strategies are established to promote tourism in order to exploit tourism resources to generate opportunities and improve the socioeconomic quality of the population. On the other hand, the descriptive method was applied using the survey technique where it was possible to identify several strong points such as the diversity of natural sites with a high possibility of being used to be adapted in different types of tourism or different activities. weak points such as the need to implement infrastructure because the places are not taken care of and their conservation is deteriorating, making them less and less safe and difficult to restore. Strategies are proposed that range from the use of social networks for advertising, encouragement of public and private entities for the implementation of a sustentable tourism plan; and citizen participation for the promotion of their culture and their city.